Proactive Behavior and Relational Capital Driving Competitive Advantage: Marketing Innovation as Mediator in East Lombok Craft MSMEs - Umu Rosyidah; Sulaiman; Syaifuddin; Salma Ila Salsabila; Cici Aryansi Quilim (Global Research Collaboration, 2026)
Research on MSME competitiveness has generally explored internal capabilities, relational networks, and innovation as distinct factors contributing to competitive advantage. Nevertheless, empirical evidence remains limited regarding the extent to which marketing innovation serves as a mediating pathway that connects proactive behavior and relational capital with competitive advantage, especially within locally rooted handicraft MSMEs. Accordingly, this study investigates the influence of proactive behavior and relational capital on competitive advantage, while also examining the mediating role of marketing innovation among handicraft MSMEs in East Lombok Regency. The proposed conceptual framework is grounded in the Resource-Based View (RBV) and Social Capital Theory, both of which highlight the importance of distinctive organizational resources and network-based relationships in fostering innovation and sustaining competitive advantage. Using a quantitative explanatory approach, data were collected through a survey involving 141 handicraft MSMEs and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that proactive behavior and relational capital positively affect marketing innovation and competitive advantage. However, marketing innovation does not exert a significant positive influence on competitive advantage. In addition, marketing innovation is not supported as a mediating variable in the relationship between proactive behavior and competitive advantage or between relational capital and competitive advantage. These findings suggest that proactive behavior and relational capital function more strongly as direct strategic resources for improving competitive advantage, whereas marketing innovation, in this particular context, does not act as an effective mechanism for translating these resources into competitive outcomes. From a theoretical perspective, this study extends the application of RBV and Social Capital Theory by demonstrating that innovation-oriented activities do not always convert internal capabilities and relational assets into competitive advantage. From a practical standpoint, handicraft MSMEs are encouraged to enhance proactive market-oriented actions and strengthen relational networks, while also carefully assessing the relevance, quality, and market alignment of their marketing innovation initiatives.